2008
DOI: 10.1262/jrd.19112
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of Inhibin in Female Japanese Quails (Coturnix japonica) from Hatch to Sexual Maturity

Abstract: Abstract.To clarify the cellular source and secretory pattern of inhibin in the Japanese quail during follicular development, the plasma concentrations of immunoreactive (ir) inhibin were measured from 1 to 7 weeks after hatching. Localization of the inhibin/activin α, βA and βB subunts was investigated by immunohistochemistry. To monitor development of the pituitary and ovarian functions, the plasma luteinizing hormone (LH) and progesterone concentrations were also measured. Ovarian weight increased gradually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…Previous studies have indicated that inhibins and activins have roles to play in the development and function of the avian gonads during post-hatch prepubertal life [1]. Developmental changes in inhibins have been observed in female Japanese quails, and these observations have shown that plasma ir-inhibins are significantly increased during sexual maturation [35]. In other aves, such as chickens [18,19] and ducks [14,20], there are similar developmental changes in the circulating ir-inhibin concentrations in accordance with the testicular activity.…”
Section: Sedqyar Et Al 104mentioning
confidence: 97%
“…Previous studies have indicated that inhibins and activins have roles to play in the development and function of the avian gonads during post-hatch prepubertal life [1]. Developmental changes in inhibins have been observed in female Japanese quails, and these observations have shown that plasma ir-inhibins are significantly increased during sexual maturation [35]. In other aves, such as chickens [18,19] and ducks [14,20], there are similar developmental changes in the circulating ir-inhibin concentrations in accordance with the testicular activity.…”
Section: Sedqyar Et Al 104mentioning
confidence: 97%
“…Inhibin is a glycoprotein hormone consisting of two dissimilar subunits, α and β, that are linked by disulfide bonds and selectively suppresses follicle-stimulating hormone (FSH) secretion [2]. The existence of bioactive inhibin in testis preparations [3,4] and ovarian granulosa cells [5,6] has been reported. The effect of induction of ovarian regression and removal of ovarian follicles on plasma inhibin indicate that the ovary is the major source of inhibin in the hen [7,8].…”
mentioning
confidence: 99%
“…The Japanese quail ( Coturnix japonica ) is considered an ideal biological and experimental model due to its fast development. Quails reach sexual maturity at 6–7 weeks old (Ball and Balthazart 2010 ; Sedqyar et al 2008 ). In the maturing male, testosterone concentrations, testicular weight, and cloacal gland area increase dramatically between 26 and 35 days of age then increase rapidly until sexual maturity.…”
Section: Introductionmentioning
confidence: 99%